2005
DOI: 10.1007/s10350-004-0798-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pudendal Block on Voiding After Hemorrhoidectomy

Abstract: A pudendal nerve block with bupivacaine results in fewer postoperative voiding complications and less pain compared with the traditional spinal anesthesia in a hemorrhoidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 15 publications
0
58
0
12
Order By: Relevance
“…For example, caudal and spinal anesthesia frequently cause urinary retention due to disruption of the micturition reflex. Kim et al 2005 showed a significantly lower rate of postoperative urinary retention in hemorrhoidectomy patients who received PNB instead of spinal anesthesia (7.5% compared with 69.6%), as well as a smaller required volume of analgesic and significantly longer and more effective postoperative pain control in the PNB cohort [2]. Similarly, Imbelloni et al 2007 demonstrated spontaneous micturition in 98 of 100 hemorrhoidectomy patients after PNB [3].…”
Section: Conflict Of Interestmentioning
confidence: 90%
See 3 more Smart Citations
“…For example, caudal and spinal anesthesia frequently cause urinary retention due to disruption of the micturition reflex. Kim et al 2005 showed a significantly lower rate of postoperative urinary retention in hemorrhoidectomy patients who received PNB instead of spinal anesthesia (7.5% compared with 69.6%), as well as a smaller required volume of analgesic and significantly longer and more effective postoperative pain control in the PNB cohort [2]. Similarly, Imbelloni et al 2007 demonstrated spontaneous micturition in 98 of 100 hemorrhoidectomy patients after PNB [3].…”
Section: Conflict Of Interestmentioning
confidence: 90%
“…The pudendal nerve exits through the greater sciatic foramina inferior to the piriformis muscle, crosses the posterior aspect of the sacrospinous ligament at the level of the ischial spine, and reenters the pelvis through the lesser sciatic foramina, then courses through Alcock's canal posteroinferiorly and divides into the inferior rectal nerve, perineal nerve, and the dorsal nerve of the clitoris or penis. The analgesic efficacy of the PNB during anorectal and urologic procedures arises from blocking the inferior rectal nerve, which supplies perianal skin, anoderm, and the external anal sphincter, and the perineal nerve, which has a superficial branch that supplies the labia or scrotum and a deep branch that supplies the external anal sphincter and urethral sphincter and mucosa [2,8]. Multiple approaches to the PNB have been described, including transvaginal, transperineal, transgluteal, and transrectal routes [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite penile anaesthesia following PNB, urinary retention and other annoying post-operative voiding complications are not common (17).…”
Section: Discussionmentioning
confidence: 99%